Open and Interactive NMS for Network Monitoring in Software Defined Networks - Aparcana-Tasayco, Andres J. (2022)
Software Defined Networking (SDN) is a technology where the programmability paradigm is applied and its study is very important in the training of future telecommunications specialists to understand other emerging technologies such as 5G, IoT and SD-WAN. In the new normal, generated by COVID-19, university students will return to data networking laboratories in a semi-presential scenario. Having a network monitoring system (NMS) application that shows in a complete way, in real time and open to new requirements, the scenarios that are implemented, is important for the training of future telecommunications specialists. In the present research work, the proposed monitoring system makes use of non-relational database, OpenDayLight as SDN controller and an architecture that uses a server that asynchronously displays the results on a client with the use of NeXt-UI. Our contribution is to have a system that allows a better visualization of the SDN scenarios developed and that facilitates students to make improvements to understand the operation of these SDN networks.